The Influence of Assistance with Media Booklet on Maternal Behavior in Feeding Stunting Toddlers (Study in The Working Area of Karangdadap Health Center pekalongan Regency) - Khikmah Wati; Apoina Kartini; Mohammad Zen Rahfiludin (Universitas Aisyah Pringsewu, 2021)
Stunting is a global problem that requires comprehensive treatment, one of which is changing the behavior of mothers in feeding stunting toddlers. Behavioral changes can be done through the provision of health education in the form of mentoring and booklets. Research agreed to find out the influence of mentoring with booklet media on maternal behavior in feeding stunting toddlers in working area Puskesmas Karangdadap Pekalongan Regency. This type of research is quasi-experiment with pretest-posttest design with the control group. The study sample was 58 mothers who had stunting toddlers in the working area of Karangdadap Health Center in Pekalongan Regency with purposive sampling techniques. Research instruments are questionnaires and booklets. Data analysis uses frequency distribution and independent t-tests. The results showed that in the intervention group, 89.7% of people aged 20-35 years, as well as in the control group, all 100% of people aged 20-35 years. The majority of the intervention group respondents' jobs were out of work (58.6%), while in the control group the majority of respondents' jobs were labourers (37.9%) and non-workers at 37.9%. The majority of the education level of intervention group respondents was primary education which was 22 people (75.9.8%) as well as in the control group it is known that the majority of respondents are basic educated, namely 16 people (56.2%). Respondents who had 1 child under five in the intervention group (69%) were larger than the control group (51.7%) Feeding behavior in stunting toddlers in the intervention group was known before being given mentoring and booklet there were 15 people (51.7%) had enough behavior and 14 people (48.3%) had less behavior. Respondents after being given mentoring and booklets who have enough behavior by 19 people (65.5%) and good behavior by 10 people (34.5%). Feeding behavior in stunted toddlers in the control group was known before counselling there were 15 people (51.7%) who had sufficient behavior and 14 people (48.3%) who had less behavior. Feeding behavior in stunting toddlers after being given health counselling is known 27 people (93.1%) have enough behavior and 2 people (6.9%) have good behavior. There is a difference between mentoring with media booklet and counselling to maternal behavior in feeding stunting toddlers in the working area of Karangdadap Health Center pekalongan regency with a value of 0.001 less than 0.05. Mentoring and booklets are more effective than counselling in improving feeding behavior in stunting toddlers. It is recommended for policymakers that in drafting health promotion program policies as an effort to improve feeding behavior in stunting toddlers can use effective promotional media such as mentoring and booklet.